TATA GUNA LAHAN PANTAI DAN RESIKO LALU LINTAS PADA KAB. BATAENG SULAWESI SELATAN - Wunas, Shirly; Natalia, Venny Veronica (FSTPT Indonesia, 2015)
Cultivating seaweed grow strong along the coast of Bantaeng Regency, mainly in Tappanjeng, Palantikang Letta, Lembang and Lamala Thus production centers are growing with working group of fishermen community. Activities are growing stronger in the arterial roadside along the coast and also in set back line. The impact is the risk of traffic accidents, caused by the activities such as: rope seed and product carriage have to cross the arterial road. The purpose of this discussion is to analyse transport network and modes to seaweed activity. Datas obtained from interviews with seaweed Farmers/Fishermen who live along arterial roads. Also from Farmers/Fishermen who were drying seaweed production. The result showed arterial network capacity is still adequate in Bantaeng. Traffic volume is relatively low together with traffic accidents, although the accessibility of fishing is very strong on arterial road. In the future needs to arrange and develop river transport for seaweed farmer’s residential also to accommodate seaweed seed binding and drying activity in some watersheds, namely Kaili, Biyangloe, and others.